Uso del software Non Visual Desktop Access para la inclusión educcativa de los estudiantes invidentes del instituto de Educación Especial para sordos y ciegos de la ciudad de Machala, del periodo académico 2013-2014. - Bustamante Ochoa, Danny Andrés (2014)
Laws supporting educational inclusion in accordance with the Constitution of Ecuador, the Organic Law on Intercultural Education, the Organic Law on Disabilities, and the United Nations Educational, Scientific and Cultural Organization approach have also been investigated. Culture.